ANALISIS MATERI IPS DALAM PEMBELAJARAN IPAS KURIKULUM MERDEKA DI SEKOLAH DASAR - Husnah, Asmaul; Fitriani, Asty; Fitri Patricya; Modesta; Handayani, Tiara Putri; Arita Marini (Bajang Institute, 2023)
This research aims to analyze social studies material in science learning in elementary school which includes adaptations of science, CP, TP and ATP learning in the Merdeka Curriculum. The method implemented in this research is literature that is closely related to learning in elementary schools, namely science, social studies, san science and other relevant theories. Based on the analysis results, CP, TP, and ATP in IPAS are important components that have been designed sequentially in each phase so that learning can be more meaningful. Technical Social studies learning in IPAS requires the role of educators to ensure that social studies learning not only teaches facts, but also encourages deeper understanding and the development of critical thinking skills. Apart from that, the role of educators in social studies learning in elementary schools must also emphasize an interactive and learner-centered approach so that with this role, students can gain more in-depth understanding and understand concepts in a more interesting way.